Effects of long-haul travel and the Olympic Games on heart rate variability in a Rugby Sevens team - Flatt, A.; Howells, D. (The Journal of Strength and Conditioning Research, 2021)
Travel stress, time zone changes and pre-competition anxiety makes peaking for Olympic competition an exceedingly complex challenge for sports teams. Purpose: To assess the impact of long-haul travel and Olympic competition on heart rate variability (HRV) and subjective well-being in a rugby sevens team. Methods: Players (n = 12; 185 ± 7 cm; 91 ± 7 kg) performed daily post-waking HRV recordings (natural log of the root mean square of successive differences, LnRMSSD) for 60 seconds in the seated position. Players also reported daily ratings of perceived sleep quality, energy, soreness, mood, and recovery on a 10-point scale. Subjective data were averaged across categories and transformed to provide a global wellness index (LnWellness). Session rating of perceived exertion (sRPE) was used to quantify loads from resistance training, rugby training and competitions. Two flights were taken on day 1 to travel 9,006 km (3 hours time gain) to Belo Horizante, Brazil for a one-week camp. Travel and time change prohibited HRV recordings on day 2. One flight was taken on day 8 to the Olympic Village in Rio (442 km). Opening ceremonies were attended on day 9, delaying bedtime by ~2 hours. Olympic tournament matches occurred on days 13-15. Undefeated, the team advanced to the gold medal final. Various strategies were implemented by support staff to minimize the physiological and psychological impact of the events leading up to and including the Olympic Games. Adjustments in sleep, wake, and training times were made in the days prior to relocation to facilitate time zone adaptation. Specific sleep schedules and nutritional strategies were implemented during flights to maintain circadian rhythm adjustments made in the days prior to departure. Strategically timed recovery sessions including mobility and stretching, pool sessions, or cryotherapy were performed. Mental skills were developed with aims of being the most resilient and adaptable team at the tournament. Changes in outcome variables relative to baseline were assessed with linear mixed models and effect sizes (ES). Results: There were no changes in LnRMSSD across time (P = 0.07) and only small ES reductions were observed on days 1, 3, 4, 10 and 14 (ES = -0.31 to -0.59). LnWellness was reduced on day 1, and increased on day 13 (P < 0.05). Mean and 95% confidence interval for LnRMSSD, LnWellness, and sRPE are presented in Figure 1. Conclusions: Long-haul travel and Olympic competition caused minimal physiological (i.e., autonomic) and psychological disturbance among players. Maintenance of status markers may reflect the effectiveness of the strategies implemented by support staff. Practical Applications: Strategic timing and implementation of sleep, nutritional, psychological, recovery, and priming interventions can help maintain player well-being, mitigate expected decrements in autonomic activity, and facilitate peak performance in rugby sevens players travelling to and competing in the Olympic Games.